CONCEPTUAL PROVISIONS OF THE STATE POLICY OF ENSURING THE ECONOMIC SECURITY OF UKRAINE IN THE CONDITIONS OF MODERN THREATS AND DIGITALIZATION - GARAFONOVA, OLGA; POLISHCHUK, LIYDMYLA; DYKHNYCH, LIUDMYLA; YASHCHENKO, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article focuses on the relevance of identification and typology of modern risks and threats to the economic security of Ukraine. According to the nature of modern risks and threats, they are classified as hybrid. The hybrid nature of modern threats to Ukraine’s economic security necessitates the application of new approaches to the formation and implementation of state policy to ensure the economic security of Ukraine’s national economy. It is shown that the economic security of the state is a complex dynamic system that requires constant monitoring and management of resilience to internal and external threats in order to ensure a positive impact on socio-economic development, improve macroeconomic development, ensure quality and necessary structural changes and institutional reforms. formation of the system of competitiveness of the national economy. Under such conditions, the general goal of state policy should be to improve Ukraine’s economic security system, ensure a higher level of its resistance to the impact of hybrid risks and threats, factors and conditions of globalization and the world order. The elements of the state policy of economic security of Ukraine are determined, namely - the initial conditions, the purpose of state policy, goals and principles of policy, directions of formation of the system of counteraction to security threats, financial-resource and organizational-managerial support. The practical significance of the research results is that the immaturity of the integral system of economic security of the state is identified, which is due to the imperfection of the institutional environment, the imbalance of its structure, the predominance of the role of informal institutions over formal ones. The scientific novelty of the study is to substantiate the conceptual provisions of state policy to ensure the economic security of the state in the face of non-standard hybrid risks and threats.